Survival rate and prognostic factors of survival among chronic myeloid leukaemia adults after initiation of tyrosine kinase inhibitor therapy in Hospital Ampang, Selangor - Ali, Zakiah Bakar (2024)
Introduction: Chronic Myeloid Leukaemia (CML) management has been revolutionized by the advent of tyrosine kinase inhibitors (TKIs). Despite more than two decades since the introduction of TKIs in the Malaysian healthcare landscape, long term outcomes have not been rigorously studied. Various factors may impact prognosis and understanding these factors may influence patient management and improve long term outcomes. Objective: This study aims to estimate and compare the 10-year overall survival (OS) rates and to identify significant prognosis factors among adults diagnosed with CML on TKI therapy in Hospital Ampang, Selangor. Methods: This retrospective cohort study reviewed the medical records of 389 CML patients aged 18 years and above who were initiated with TKIs – including imatinib mesylate or nilotinib – between 2012 and 2021, while patients who received hematopoietic stem cell transplantation (HSCT) therapy and transferred out were excluded. The primary outcome of interest was an event of death from any cause. Censored observations were considered for patients who remained alive at the end of the study or those who were lost to follow-up (LTFU). Survival time was the duration of time (months) from the initiation of TKI therapy in CML patients to the event. Kaplan-Meier product limit estimator and log-rank test were applied for univariable analysis, while Cox proportional hazards regression was applied in multivariable analysis to identify the significant prognostic factors for survival. Results: There were 51 deaths (13.1%). Patients were followed up for a median of 74 months (interquartile range (IQR): 58 months) with a 10-year overall survival rate of 81.7%. The overall survival rates were significantly better for age <60 years at the TKI therapy initiation (p<0.001), Charlson Comorbidity Index 2–3 (p<0.001), baseline blasts <10% (p<0.001), low-risk prognosis scoring with EUTOS long-term survival score (ELTS) (p=0.001), chronic phase (CML-CP) at diagnosis (p<0.001), no CML disease progression (p<0.001), year of TKI therapy initiation between 2012–2015 (p<0.001), standard dose initial TKI regimen (p=0.041), high medication possession ratio (MPR) for TKI (p<0.001), no adverse events requiring TKI dose adjustment (p=0.002), no history of follow-up defaults (p=0.015), not more than three concurrent medications with TKI therapy (p<0.001), no TKI switching (p=0.029), complete cytogenetic response (CCyR) at 6 months (p=0.035), major molecular response (MMR) at 12 months (p=0.035), and 24 months (p<0.001). Four significant independent prognostic factors of survival among CML adults with TKI therapy identified were CML disease progression (adjusted hazard ratio (AHR)=8.43; 95% confidence interval (CI): 3.95, 18.01; p<0.001), time to TKI initiation (100 days) (AHR=1.22; 95% CI: 1.11, 1.35; p=0.011), three or more concurrent medications with TKI therapy (AHR=7.59; 95% CI: 3.62, 15.91; p<0.001) and failure to achieve MMR at 24 months (AHR=2.19; 95% CI: 1.04, 4.64; p=0.039). Conclusion: The study emphasizes the importance of therapy initiation and close monitoring for patients experiencing CML disease progression, delayed TKI commencement post-diagnosis, three or more concurrent medications alongside TKI, and failure to achieve MMR at 24 months to ensure improved long-term outcomes and overall survival.